Oncocytic adrenocortical neoplasm arising from adrenal rest in the broad ligament of the uterus. (April 2014) - Kasajima, Atsuko; Nakamura, Yasuhiro; Adachi, Yuzu; Takahashi, Yayoi; Fujishima, Fumiyoshi; Chiba, Yutaka; Uehara, Shigeki; Watanabe, Mika; Sasano, Hironobu
<x xml:space="preserve">Abstract</x> Oncocytic adrenocortical neoplasm is characterized by abundant eosinophilic cytoplasm containing mitochondria, occasional nuclear atypia and diffuse growth pattern. Oncocytic adrenocortical neoplasm arising in adrenal rest is, however, extremely rare. We report a case of oncocytic adrenocortical neoplasm arising in adrenal rest of the broad ligament with associated marked lipomatous metaplasia. A well circumscribed tumor was accidentally detected in the pelvic cavity of a 29 year old Japanese woman, adjacent to the broad ligament of the uterus. The tumor was composed of large eosinophilic cells associated with diffuse growth pattern and abundant mature adipose tissue admixed with foci of clear cells. Both steroidgenic factor 1 (SF‐1) and alpha‐inhibin were immunohistochemically positive in tumor cells. Abundant mitochondria detected by immunohistochemical and electron microscopic examination confirmed the diagnosis of oncocytic adrenocortical neoplasm. The absence of necrosis, capsular and vascular invasion as well as the low mitotic index indicated the benign potential of this tumor. The tumor cells were also positive for dehydroepiandrosteron‐sulfotransferase (DHEA‐ST), 17β‐hydroxysteroid dehydrogenase type 5 (17β‐HSD5), 3β‐hydroxysteroid dehydrogenase (3β‐HSD) and steroid 17α‐hydroxylase (P450‐c17), suggesting a possible production of testosterone of this tumor. This is the first reported case of oncocytic adrenocortical adenoma arising in adrenal rest of the broad ligament.